Efeito tripanocida do (-)-alfa-bisabolol sobre a cepa y de Trypanosoma cruzi - Menezes, Ramon Róseo Paula Pessoa Bezerra de (2017)
Chagas disease is a major public health problem, and the drugs available possess limited efficacy and great toxicity. In this way, there is a pungent need of new drugs. The aim of this work was to evaluate the trypanocidal effect of (-)-α-bisabolol (BIS) over the life forms of Trypanosoma cruzi and investigate its selectivity and mechanism of action. BIS cytotoxicity over mammalian cells was evaluated over LLC-MK2 cells, using MTT assay. BIS caused cytotoxic effect only at 1000 and 500 µM, with CC50 = 528 ± 34 µM. Then the antiparasitic effect was investigated over epimastigote, which demonstrated a progressive and time- and concentration-dependent effect, with IC50/24h = 285 ± 20 µM; IC50/48h = 144.7 ± 8.6 µM; IC50/72h = 97.33 ± 3.25 µM; e IC50/96h = 59.8 ± 4.5 µM. Over trypomastigotes, BIS caused effect at all tested concentrations, with LC50 = 20 ± 3.84 µM. Using CC50 and LC50 values, selectivity index was estimated at 26.5. BIS also presented antiamastigote activity, with decrease on the percentage of infected cells, the number of amastigotes per infected cells and survival index. Besides, BIS caused its effects even when incubated by few time periods, as shown by growth recovery experiments. By flow cytometry, it was demonstrated that BIS trypanocidal effect was associated with apoptosis induction, increase on reactive oxygen species and loss of mitochondrial transmembrane potential. Also, swelling of reservosomes was present al late stages. Scanning electronic microscopy evaluation showed parasites with loss of typical format and with membrane pores. Finally, the interaction of BIS with tcGAPDH (Glyceraldehyde-3-phosphate dehydrogenase from T. cruzi) was evaluated by both theoretical and experimental methods. Docking simulation demonstrated possible interaction between tcGAPDH and BIS, which it was confirmed by enzymatic assay. In conclusion, it was demonstrated that BIS possess antiparasitic effect over Trypanosoma cruzi strain Y life forms, with possible induction of apoptosis and oxidative stress. Also, inhibition on tcGAPDH appears to be associated with this effect.